2020
DOI: 10.1111/cpr.12869
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharide from Cryptococcus heimaeyensis S20 induces autophagic cell death in non‐small cell lung cancer cells via ROS/p38 and ROS/ERK signalling

Abstract: Objectives Cryptococcus heimaeyensis S20 is found in Antarctica and can produce exopolysaccharides (CHEPS). Here, we explore the anti‐tumour effects of CHEPS on non‐small cell lung cancer (NSCLC). Materials and methods Cell viability was assessed by CCK8 and colony formation assays. Flow cytometry was used to analyse the cell cycle, cell apoptosis and reactive oxygen species (ROS). Cell autophagy was detected by EGFP‐LC3 puncta assay, Lyso‐Tracker Red staining and transmission electron microscopy. mRNA and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…However, there might be some downstream signaling pathways involved in this process. Previous studies have shown that p38 MAPK and p44/42 MAPK (Erk1/2) signaling pathways are mainly downstream of ROS in various pathological processes ( 32 , 33 ), and the NF-κB signaling pathway can be activated by IS in the kidney ( 26 ). So we investigated the changes of p38 MAPK, p44/42 MAPK, and NF-κB signaling pathways in IS-treated rats and NRVMs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there might be some downstream signaling pathways involved in this process. Previous studies have shown that p38 MAPK and p44/42 MAPK (Erk1/2) signaling pathways are mainly downstream of ROS in various pathological processes ( 32 , 33 ), and the NF-κB signaling pathway can be activated by IS in the kidney ( 26 ). So we investigated the changes of p38 MAPK, p44/42 MAPK, and NF-κB signaling pathways in IS-treated rats and NRVMs.…”
Section: Resultsmentioning
confidence: 99%
“…Mitrokhin et al found that IL-2–induced phosphorylation of NF-κB upregulated the nonselective conductance in human cardiac fibroblast ( 60 ). Because p38 MAPK, p44/42 MAPK, and NF-κB signaling pathways can regulate the changes of some ion channel current, and p38 MAPK and p44/42 MAPK are the main downstream signaling pathways of ROS in some pathological processes ( 32 , 33 ), we speculated that IS might regulate p38 MAPK, p44/42 MAPK, and NF-κB signaling pathways through ROS production and further cause the changes of I to,f -related proteins and I to,f densities. The main proteins of p38 MAPK, p44/42 MAPK, and NF-κB signaling pathways were detected by Western blot.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular pathways that are regulated by ROS are of importance in cancer therapy [62][63][64]. Increased ROS generation leads to the activation of p38 and extracellular signal-regulated kinase (ERK), which subsequently stimulates cell death and cell cycle arrest at S and G2/M phases [65]. Organelles are vital targets of ROS in cancer cells.…”
Section: Ros Role In Cancermentioning
confidence: 99%
“…pBFRF1-Myc, pIKKi-HA, pBZLF1-HA (Zta-HA), and pBGLF4-HA were also constructed with similar methods, using pMyc-N1 or pHA-N1 vector (regenerated from pEYFP-N1, Clontech). Besides, one pair of oligonucleotide sequences 5′-GGG TCT CTC AAC GGA TGT TGA and 5′-CTC AAC TCA CGT GTC TAG TGT C (38)(39)(40)(41)(42)(43)(44) was inserted into the good RNAi product of Oligoengine pSuper-retro-puro (Oligoengine) that can effectively remove off-target of the target gene, to construct RNA interference expression plasmids pSuper-shBFRF1-retro-puro and pSuper-shRandom-retro-puro [a good off-target control (45)(46)(47)(48)], respectively. Other gift plasmids were provided by Drs.…”
Section: Plasmids Constructionmentioning
confidence: 99%